Building brand authenticity 7 habits of iconic brands - Beverland, Michael (Houndmills, Basingstoke, Eng. Palgrave Macmillan, 2009)
"The projection of authenticity is one of the key pillars of marketing. Research reveals that consumers seek authenticity through the brands they choose. This book proposes to do so. Based on extensive research with consumers and brand managers this book offers seven guiding principles for building brand authenticity"--Provided by publisher.
Machine generated contents note: Introductionthe crisis of branding and the demand for authenticity -- What is authenticity? -- Principle 1Tell compelling brand stories -- Principle 2Appear as artisanal amateurs -- Principle 3Stick to your roots -- Principle 4Love of product and production -- Principle 5Market Immersion -- Principle 6Cultural contribution -- Principle 7Indoctrinate staff into the cult -- A call to actionbuilding brand authenticity Introductionthe crisis of branding and the demand for authenticity -- What is authenticity? -- Principle 1Tell compelling brand stories -- Principle 2Appear as artisanal amateurs -- Principle 3Stick to your roots -- Principle 4Love of product and production -- Principle 5Market Immersion -- Principle 6Cultural contribution -- Principle 7Indoctrinate staff into the cult * A call to actionbuilding brand authenticity.
Keywords: Branding (Marketing); Brand name products